Different types of foot orthoses effect on gait mechanics in patients with rheumatoid arthritis. (June 2022) - Simonsen, Morten Bilde; Hirata, Rogerio Pessoto; Næsborg-Andersen, Ketill; Leutscher, Peter Derek Christian; Hørslev-Petersen, Kim; Woodburn, James; Andersen, Michael Skipper
Abstract: Foot orthoses are a first line conservative treatment for foot impairments in patients with rheumatoid arthritis (RA), however their effect on gait mechanics is poorly understood. We aimed to compare changes in lower limb and foot mechanics between two types of commonly used foot orthoses (FO) with a control. Twenty-seven patients with rheumatoid arthritis participated in this crossover study. Two different types of FO (a medially wedged custom-made FO and a prefabricated FO with a metatarsal dome, respectively), were compared against a control insole. During gait, lower limb mechanics were analyzed using 3D motion capture, force plates, and an in-shoe pressure system. Inverse dynamics models were created in the Anybody Modeling System to calculate joint angles and joint moments during gait. Gait variables were analyzed using statistical parametric mapping. Compared to the control, the prefabricated FO had limited effect on gait mechanics. Compared to the control the custom-made FO reduced ankle plantarflexion moment with 0.4 %body weight * body height (BW * BH) between 66 and 76% of stance and ankle eversion moment was reduced 0.16% BW*BH between 3 and 40% of stance. Furthermore, it also reduced the average forefoot plantar pressure by 9 kPa between 20 and 62% of stance compared to the control. Changes in foot pressure distribution, joint moments and angles were most pronounced for custom-made FO compared to the prefabricated FO. The findings suggest that patients with RA and foot impairments may benefit more from an individualized FO strategy, if the aim of the treatment is to alter gait mechanics. (NCT03561688).